Capture and sequencing of NAD-capped RNA sequences with NAD captureSeq - Winz, Marie-Luise; Cahová, Hana; Nübel, Gabriele; Frindert, Jens; Höfer, Katharina; Jäschke, Andres (Nature protocols, 2017)
Here we describe a protocol for NAD captureSeq that allows for the identification of nicotinamide-adenine dinucleotide (NAD)-capped RNA sequences in total RNA samples from different organisms. NAD-capped RNA is first chemo-enzymatically biotinylated with high efficiency, permitting selective capture on streptavidin beads. Then, a highly efficient library preparation protocol tailored to immobilized, 5′-modified RNA is applied, with adaptor ligation to the RNA's 3′ terminus and reverse transcription (RT) performed on-bead. Then, cDNA is released into solution, tailed, ligated to a second adaptor and PCR-amplified. After next-generation sequencing (NGS) of the DNA library, enriched sequences are identified by comparison with a control sample in which the first step of chemo-enzymatic biotinylation is omitted. Because the downstream protocol does not necessarily rely on NAD-modified but on 'clickable' or biotin-modified RNA, it can be applied to other RNA modifications or RNA-biomolecule interactions. The central part of this protocol can be completed in ∼7 d, excluding preparatory steps, sequencing and bioinformatic analysis.